BIMBINGAN KELOMPOK SEBAGI ALTERNATIF UNTUK MENINGKATKAN KOMUNIKASI INTERPERSONAL SISWA (Jurnal Pelangi : Research of Education and Development, 2014)
Interpersonal Communication is a social process by which individuals are engaged in them influence each other. The phenomenon that occurs in students associated with interpersonal communication is a lot of misunderstanding when students have problems communicating, mutual understanding is often not the case when students interact with other students. Group counseling services are in guidance and counseling services that can be used to improve students' interpersonal communication. By conducting group counseling services, students will be given the understanding and practice of communication interpsersonal. This study aims to reveal the effectiveness of group counseling services in improving students' communication interpersonal communication